PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN PRESTASI BELAJAR - Jaminah (UNIB Press, 2022)
The study aims to describe the model problem based learning can increase students’ critical thinking ability and learning performance at an eight-grade Math course at MTs Al-Azhar Pagaralam, and the effectiveness of the model problem based learning can improve students’ learning performance. The study is a class action study performed int three cycles then followed by mastering the experiment. Each cycle consists of four stages of planing, action, observation, and reflection. The Subject of this study is the VIII grader at MTs Al-Azhar Pagaralam of the year 2021/2022. Data collection techniques via observation and testing. Data analysis techniques using average formulas ant t-tests. Problem based learning has concluded that the application of the model problem based learning can improve students' critical thinking ability and learning performance, and it effectively enhances eighth grade student learning at MTS al azhar Pagaralam